Effect of Calina Papaya Leaves Extract on Respiratory Tract in Cigarette Smoke Exposed Rats - Haris Setiawan; Arlinda Sekar Ayu Hikmawati; Sri Wijayanti Wulandari; Eriza Via Malinda; Ichsan Luqmana Indra Putra (UIN Sunan Gunung Djati Bandung, 2022)
Cigarette smoke is a source of free radicals that cause health problems throughout the world. Indonesia is a country that has many sources of natural antioxidants in counteracting free radicals, one of which is Calina papaya leaves. The study aimed to determine the potential of Calina papaya leaves antioxidants in improving the respiratory organs of Wistar rats after being exposed to cigarette smoke. The study using 25 male Wistar rats consisted of Control (not exposed to cigarette smoke and given distilled water), KN (cigarette smoke and given distilled water), P1 (cigarette smoke and Calina Papaya Leaves Ethanolic extracts (CPLE) 100 mg/kg BW), P2 (cigarette smoke and CPLE 200 mg/kg BW), and P3 (cigarette smoke and given CPLE 300 mg/kg BW). Exposure to cigarette smoke and administration of extracts was carried out for 21 days. On day 22, the rats were euthanized and dissected to remove the lungs and trachea. Organs were prepared using the paraffin method and hematoxylin-eosin staining. Parameters consisted of histopathological observations of the lungs and trachea. All data parameters were analyzed using a one-way ANOVA test and Duncan's advanced test (p<0.05). The results showed that there was an improvement in histopathology of the lungs and trachea at a dose of 200 mg/Kg BW compared to other doses (p<0.05). The study showed that the Calina papaya leaves ethanolic extracts have the potential as a source of antioxidants in improving the respiratory organs of Wistar rats after being exposed to cigarette smoke.